Revolving Forcep Technique for Subretinal Band Removal - Kaustubh Rewatkar; Amit S. Nene; Smitesh Shah; Pushpanjali Badole; Prateek Shenoy; Onkar H. Pirdankar (Delhi Journal of Ophthalmology)
Subretinal bands (SRBs) are a form of proliferative vitreoretinopathy which is usually seen associated with chronic retinal detachment. SRBs prevent retinal reattachment after the surgery and thus it needs to be removed. Here, we report a novel technique of removing the SRB.